Does the primary soft-tissue sarcoma configuration predict configuration of recurrent tumors on magnetic resonance imaging?. (May 2022) - Sedaghat, Sam; Ravesh, Mona Salehi; Sedaghat, Maya; Meschede, Jens; Jansen, Olav; Both, Marcus
Background: Soft-tissue sarcomas (STS) are rare malignancies of the soft tissue. Purpose: To assess whether the magnetic resonance imaging (MRI) configuration of primary STS can predict the configuration of a recurring tumor and whether the MRI configuration of multiple recurrences differs in one and the same patient. Material and Methods: Thirty-nine patients with histologically proven recurrent STS were included in this retrospective study and underwent pre- and post-treatment MRI. Three main configurations of primary and recurrent tumors were identified: polycyclic/multilobulated; ovoid/nodular; and streaky. Results: Sixty recurrent lesions were detected: 34 ovoid/nodular; 15 polycyclic/multilobulated; and 11 streaky. Five recurrences were multifocal and eight were bifocal. Of 39 patients, 28 (71.8%) presented one recurrence within the MRI follow-up period ( P  = 0.006); in 10 patients (25.6%), up to three different configurations of recurring STS were identified in one patient. Recurrences of polycyclic/multilobulated primaries were mostly ovoid/nodular (48%; P  = 0.003) or polycyclic/multilobulated (37%; P  = 0.014), and recurring ovoid/nodular STS significantly most often showed the same configuration as the primary tumor (85%; P  < 0.001). Primary STS with a streaky configuration recurred in all three configurations in roughly equal proportions. Homogeneity/heterogeneity and tumor borders are significantly associated with the configuration of recurrences. Conclusion: Primary STS configuration may help predict recurrent tumor configuration when the primary STS had a polycyclic/multilobulated or ovoid/nodular configuration. However, recurrent STS configuration can also differ from primary STS configuration, especially when the primary STS had a streaky configuration, rendering recurrent STS difficult to predict. Different configurations of recurrent STS in one and the same patient are common.